Implementation of the Internet of Things in the Design and Development of a Three-Phase Power Monitoring System - Nengsih, Sri; Hidayati, Noura (PTE FTK UIN Ar-Raniry, 2025)
This research aims to design an IoT-based three-phase electrical power monitoring system, evaluate its performance, and compare it with manual measurements. The system is developed by using microcontroller-based sensors to measure voltage, current, and power parameters in real-time. The methodology used is the 4D model, simplified into three stages: define, design, and development. In the define stage, issues related to the inefficiency of conventional monitoring were identified. The design stage involved creating a system diagram incorporating components such as the PZEM-004T sensor, ESP8266 microcontroller, LCD I2C 16x2 display, and the Blynk application for real-time data visualization. The development stage included system construction, testing, and validation by four media experts, yielding a validation score of 92%, indicating that the system is highly feasible for use. The results indicate that the IoT-based monitoring system effectively measures three-phase electrical parameters, with real-time data displayed on both an LCD screen and the Blynk application for remote access. Compared to conventional monitoring methods, the system offers greater efficiency and responsiveness. Overall, the research stated has successfully enhanced the accuracy and convenience of three-phase power monitoring.